PENINGKATAN PRODUKTIVITAS KACANG TANAH DI LAHAN KERING MELALUI APLIKAS - Asis Asis; M. Ramlan; Muhammad Ismail; Lamhot Edy Pakpahan; Sutarni; Abdurahman (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2022)
[IMPROVEMENT OF PEANUT GROWTH AND PRODUCTIVITY IN DRY LAND THROUGH THE APPLICATION OF DOLOMITE AND NPK FERTILIZERS]. Dry land is commonly characterized by low pH and nutrient availability for peanut growth. Therefore, application of dolomite and NPK fertilizer might correct its characteristics. This study aimed to determine the appropriate dose of dolomite and NPK fertilizers to increase growth and productivity of peanut in dry land. This study was carried out from November 2019 to February 2020 at the Meteorological, Climatological, and Geophysical Agency, Indrapuri Experimental Garden, Aceh Besar, Aceh and used a randomized block design (RBD) with two factors and three replications. The first factor was three dosages of dolomite (i.e., 0, 250, and 500 kg/ha) and the second factor was three levels of NPK fertilizers (i.e., 0 kg/ha Urea+ 0 kg/ha SP36+ 0 kg/ha KCl), 25 kg/ha Urea + 50 kg/ha SP36 + 50 kg/ha KCl, and 50 kg/ha Urea + 100 kg/ha SP36 + 100 kg/ha KCl). The results showed that application of dolomite or NPK fertilizers had a significant effect on peanut yield components. Application of dolomite at 500 kg/ha or NPK fertilizers at 50 kg/ha Urea + 100 kg/ha SP36 + 100 kg/ha KCl increased peanut productivity by 10% and 9.23%, respectively compared to the control.